Snow properties at the forest–tundra ecotone: predominance of water vapor fluxes even in deep, moderately cold snowpacks - Lackner, Georg; Domine, Florent; Nadeau, Daniel F.; Lafaysse, Matthieu; Dumont, Marie (The Cryosphere, 2022)
The forest–tundra ecotone is a large circumpolar transition zone between the Arctic tundra and the boreal forest, where snow properties are spatially variable due to changing vegetation. The extent of this biome through all circumpolar regions influences the climate. In the forest–tundra ecotone near Umiujaq in northeastern Canada ( 56∘33′31′′ <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="51pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="f1db1439419f1c115d33170bc9fc3b0e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-16-3357-2022-ie00001.svg" width="51pt" height="11pt" src="tc-16-3357-2022-ie00001.png"/></svg:svg> N, 76∘28′56′′ <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="51pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="5933117e795b4e341763bad4c5c10a2e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="tc-16-3357-2022-ie00002.svg" width="51pt" height="11pt" src="tc-16-3357-2022-ie00002.png"/></svg:svg> W), we contrast the snow properties between two sites, TUNDRA (located in a low-shrub tundra) and ...